Treatment of severe acute mitral regurgitation following thoracoabdominal aortic aneurysm repair. Issue 9 (21st June 2022) - Jr Soletti, Giovanni; Perezgrovas‐Olaria, Roberto; Chadow, David; Cancelli, Gianmarco; Dimagli, Arnaldo; Reisman, Mark; Gaudino, Mario; Girardi, Leonard N.; Lau, Christopher
Abstract: An asymptomatic 63‐year‐old male with chronic type B aortic dissection underwent repair of an expanding 6.1 cm extent I thoracoabdominal aortic aneurysm. His postoperative course was complicated by respiratory failure from severe acute mitral regurgitation likely due to papillary muscle rupture, which was corrected with transcatheter MitraClip edge‐to‐edge repair.